Design, Characterisation and Performance of an Improved Portable and Sustainable Low-Field MRI System - de Vos, Bart; Parsa, Javad; Abdulrazaq, Zaynab; Teeuwisse, Wouter M.; Van Speybroeck, Camille D. E.; de Gans, Danny H.; Remis, Rob F.; O’Reilly, Tom; Webb, Andrew G. (Frontiers in Physics, 2021)
Low-field permanent magnet-based MRI systems are finding increasing use in portable, sustainable and point-of-care applications. In order to maximize performance while minimizing cost many components of such a system should ideally be designed specifically for low frequency operation. In this paper we describe recent developments in constructing and characterising a low-field portable MRI system for in vivo imaging at 50 mT. These developments include the design of (i) high-linearity gradient coils using a modified volume-based target field approach, (ii) phased-array receive coils, and (iii) a battery-operated three-axis gradient amplifier for improved portability and sustainability. In addition, we report performance characterisation of the RF amplifier, the gradient amplifier, eddy currents from the gradient coils, and describe a quality control protocol for the overall system.